Factors influencing productivities in five plastic factories at Bukit Beruntung / Akmalhakkim Mokhlas, Nurashakirah Nabila Hussin and Wan Nurul Azura Wan Mohammad - Mokhlas, Akmalhakkim; Nabila Hussin, Nurashakirah; Wan Mohammad, Wan Nurul Azura (2014)
Productivity of the organization is one of the area that must be concern in order to do continues improvement in manufacturing industries, the level of productivity is depending on various factors. In this studies researcher select 9 different factors from variety sources of previous research. The main objectives of this study is to know how strong relationship between selected independent variable which is motivation, communication, leadership behaviour, materials and tools, work environment, project characteristics, teamwork, supervision, and quality management with dependent variable, productivity in organization. From the different industries field study and several reasons, result from this study is not all significantly similar with previous research that referred by researchers. Through purposive sampling and using a sample size of 125 respondents the data will be analyse through the various related statically tools namely Cronbach's Alpha reliability Test, Pearson Correlation, and Regression Analysis. Hence, the result will be justified after all those circumstances being conducted.